Overview of Lifestyle in Hypertension Sufferers at Exemplary Community Health Centers in 2022 - Christania Romauli Silitonga; Friska Ginting; Lindawati Simorangkir (Sean Institute, 2023)
Lifestyle is a pattern of life in a person in everyday life such as activities, interests, and treatment. There are several unhealthy lifestyles through one’s living habits, for example smoking habits, irregular eating patterns, irregular physical activity or exercise, and stress. The purpose of this study was to identify the lifestyle of hypertension sufferers at the Teladan Health Center in 2022. The population in this study was hypertension sufferers at the Teladan Health Center in 2022. The sample in this study was 41 people with random sampling. The measuring instrument used is a questionnaire. Data analysis used univariate test. The results of the study based on demographic data obtained data from the age of 45-54 years (12 respondents). those with the highest education from 27 universities, sex determined by men as many as 22 respondents. Lifestyle Description of Hypertension Patients at the Model Health Center in 2022, namely the sufficient category, with a total of 22 respondents (53.7%).